2019
DOI: 10.12659/msm.912345
|View full text |Cite
|
Sign up to set email alerts
|

Early Protection by Resveratrol in Rat Lung Transplantation

Abstract: BackgroundResveratrol is a multifunctional bioactive substance that has effects in anti-inflammation and prevention of ischemia-reperfusion injury. This study compared the inflammation and expression of related proteins during the early stages after transplantation to explore the effects and mechanisms of resveratrol on transplanted lung.Material/MethodsSprague-Dawley rats were randomized to receive pretreatment of resveratrol suspension (60 mg/kg; RES group), dexamethasone (1 mg/kg; DEM group), or normal sali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Cell membrane injury and intracellular oxidative phosphorylation disorder caused by ROS during I/Rep lead to cell death, inflammation, and leukocyte chemotaxis. [ 19 ] The ROS lead to increased cell permeability and lysis by causing lipid peroxidation in the cell membrane. [ 16 ] As one of the end products of I/Rep injury, MDA emerges with the breakdown of polyunsaturated fatty acids.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cell membrane injury and intracellular oxidative phosphorylation disorder caused by ROS during I/Rep lead to cell death, inflammation, and leukocyte chemotaxis. [ 19 ] The ROS lead to increased cell permeability and lysis by causing lipid peroxidation in the cell membrane. [ 16 ] As one of the end products of I/Rep injury, MDA emerges with the breakdown of polyunsaturated fatty acids.…”
Section: Discussionmentioning
confidence: 99%
“…The RES (trans-3,4,5-trihidroksistilben) is a natural polyphenolic compound with antioxidant, anti-inflammatory, and anti-fibrotic properties. [ 19 , 21 ] The antioxidant effects of RES have been investigated in various I/Rep models and tissues. However, to the best of our knowledge, there are no previous studies investigating the effects of RES on lung tissue in the I/Rep model induced by occlusion of the IAA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Del Sorbo and colleagues suppressed apoptosis using siRNA targeting the pro-apoptotic molecule Fas, improving lung function in a mouse IRI model (58). Xu et al showed that RIPK3and MLKL-dependent necroptosis was upregulated in rat lungs undergoing IRI (59). Mingyao Liu's group showed that IRI induces necroptosis in human lung epithelial cells, and that this process could be prevented by necrostatin (inhibitor of RIPK3 mediated phosphorylation) in vitro (60); in a subsequent study, the same group showed that IRI could be prevented by administration of necrostatin in a rat orthotopic lung transplant model (61).…”
Section: Primary Graft Dysfunction: a Brief Overviewmentioning
confidence: 99%
“…Furthermore, resveratrol has been characterized with anti-microbial, neuroprotective, anti-aging, cardioprotective and anti-cancer activities both in vivo and in vitro ( Lee et al, 2018 , Li et al, 2018 ). Most recently, resveratrol was shown to protect rat lung in the early stages after lung transplantation ( Xu, Lv, Wang, Ye, & Hu, 2019 ). Although previous studies suggest that resveratrol or traditional Chinese prescriptions containing resveratrol has been practiced clinically to treat a variety of lung diseases, a comprehensive review with perspectives on the limitations of current pharmacology researches of resveratrol on lung diseases is still missing.…”
Section: Introductionmentioning
confidence: 99%